INTEGRATED ARTIFICIAL INTELLIGENCE REMOTE SMART PANDEMIC ASSESSMENT CABIN (i-RSPAC) AS ALTERNATIVE SOLUTION OF PREVENTION AND CONTROLLED THE PANDEMIC - Muhammad Fitroh Fajar Ramadhan Syarief Hidayatullah, Sonny Dhamayana Rochman (International Journal of Modern Agriculture, 2021)
As present dynamic global challenges raised and focused in how to monitor, control and prevent the escalation of pandemic; most of the countries have similar challenges to provide accessible healthcare services, pandemic monitoring and citizen health assessment to identified, monitored, and controlled the escalation of pandemic. Each country in global race era to get maximum rates of citizen population health testing as reference and identified the escalation of pandemic and get feedback information related the control measures effect, which has been taken. This research paper is part of analysis review the relationship of population testing rate with 5(five) main features to identify, mitigate and control the pandemic through provision of independent automated remote medical assessment cabin.